A case report of chylous ascites after gastric bypass for morbid obesity. (2016) - Capristo, Esmeralda; Spuntarelli, Valerio; Treglia, Giorgio; Arena, Vincenzo; Giordano, Alessandro; Mingrone, Geltrude
Highlights: Roux-en Y Gastric Bypass (RYGB) is the most commonly utilized bariatric procedure. RYGB excludes a portion of the stomach to further endoscopic examination. A case of poorly differentiated antral gastric carcinoma after RYGB is described. Diagnosis was delayed due to scarce symptomatology and confounding factors. A strict follow-up in post-RYGB patients was highly suggested for an early diagnosis of malignant gastric cancer. Abstract: Introduction: We described the case of a highly aggressive antral gastric carcinoma with a scarce symptomatology, in a patient undergone Roux-en-Y Gastric Bypass (RYGB) for obesity. Presentation of case: A 61 year-old white man in apparent good health, who underwent laparoscopic RYGB for obesity 18 months earlier, with a loss of 30 kg, reported a sudden abdominal distension and breath shortness with a weight gain of 5 kg in few days. Endoscopy of both upper gastro-intestinal tract and the colon were performed along with CT-scan and positron-emission tomography (PET) CT- scan. A biopsy of the palpable lymph node in the left supraclavicular fossa was taken for analysis. Abdominal paracentesis produced milky fluid, while citrine pleural fluid was aspirated by thoracentesis. Immunochemistry studies of the lymph node biopsy revealed tumor cells positive for cytokeratin (CK)7 and CK20, CDX2 and CAM 5.2 and negative for HER2 and TTF1 suggesting colon cancer. The colon and upper gastro-intestinal endoscopy were normal. A CT-scan and positron-emission tomography (PET) with 2-[fluorine-18]fluoro-2-deoxy-d -glucose (FDG) showed an intense FDG-uptake in the gastric antrum and in the lymph nodal chains. Given these findings, a diagnosis of poorly differentiated antral gastric carcinoma with multiple lymph node metastases was raised.The patients died 4 months after diagnosis. Discussion: RYGB is a widely performed bariatric operation and no data are reported on the risk of developing gastric cancer in the excluded stomach. Conclusion: This case report suggests that great attention should be devoted to post-RYGB patients for an early diagnosis of malignant gastric cancer.